What's the meaning of local? Using molecular markers to define seed transfer zones for ecological restoration in Norway. (6th April 2016) - Jørgensen, Marte Holten; Elameen, Abdelhameed; Hofman, Nadine; Klemsdal, Sonja; Malaval, Sandra; Fjellheim, Siri
Abstract: According to the Norwegian Diversity Act, practitioners of restoration in Norway are instructed to use seed mixtures of local provenance. However, there are no guidelines for how local seed should be selected. In this study, we use genetic variation in a set of alpine species ( Agrostis mertensii, Avenella flexuosa, Carex bigelowii, Festuca ovina, Poa alpina and Scorzoneroides autumnalis ) to define seed transfer zones to reduce confusion about the definition of 'local seeds'. The species selected for the study are common in all parts of Norway and suitable for commercial seed production. The sampling covered the entire alpine region (7–20 populations per species, 3–15 individuals per population). We characterised genetic diversity using amplified fragment length polymorphisms. We identified different spatial genetic diversity structures in the species, most likely related to differences in reproductive strategies, phylogeographic factors and geographic distribution. Based on results from all species, we suggest four general seed transfer zones for alpine Norway. This is likely more conservative than needed for all species, given that no species show more than two genetic groups. Even so, the approach is practical as four seed mixtures will serve the need for restoration of vegetation in alpine regions in Norway.